2016
DOI: 10.17586/2220-8054-2016-7-4-699-702
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influence study on copper selenide films

Abstract: Copper selenide was prepared by film is successfully deposited on a Fluorine-doped Tin Oxide (FTO) substrate by a brush plating technique. The film was uniform, had good adherence to the substrate and was annealed at 300• C and 500• C. As the annealing temperature increased, the orientation of the crystallites is more randomized than in the as-prepared film. The structural and optical properties of the film were investigated by XRD, SEM, EDAX, UV-Visible and PL. The XRD pattern indicated that this film was cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Optical characterization has been performed and band gap values were obtained for the films which revealed that the films possessed very good optical properties necessary for the materials used in solar cells [9].…”
Section: Resultsmentioning
confidence: 99%
“…Optical characterization has been performed and band gap values were obtained for the films which revealed that the films possessed very good optical properties necessary for the materials used in solar cells [9].…”
Section: Resultsmentioning
confidence: 99%